Creating a transformative space for change: A qualitative evaluation of the RHS Wellbeing Programme for people with long term conditions. (September 2021) - Howarth, Michelle; Lawler, Cormac; da Silva, Anna
Abstract: Purpose: Our research aimed to evaluate the impact of the RHS Wellbeing (WB) Programme on people with long-term conditions. Findings: A thematic analysis identified how the WB programme facilitated improved social connectivity, sense of wellbeing and purpose through the creation of a 'healthy, natural and safe space' predicated on 'person-centred approaches'. Participants felt they were 'part of something larger' which enabled 'transformation of their health and wellbeing'. Conclusions: The WB Programme offered space to grow, heal and reconnect. Losing oneself in a nature-based space can have a lasting transformative impact on individuals. Highlights: Nature-based activities can transform wellbeing of people with long term conditions. Therapeutic value relies on creation of a healthy and safe space. Person-centred activities allow for meaningful participation. Losing oneself in nature and activity can aid finding oneself in the process.